Estimated Land Lease Value Of Pt. Subasuka Go In Increasing Local Government Revenue (Pad) Kupang City (Case Study Pt Subasuka Go Pasir Panjang) - Maria Damai; Aldarine Molidya; Rikhard T.Ch Bolang (Universitas Dharmawangsa Medan, 2026)
This study aims to determine the contribution of the fair rental value of regional assets in the form of land owned by the Kupang City Government which is leased to a private party, namely PT Subasuka Go, located in Pasir Panjang Village, Kelapa Lima District, Kupang City. In determining the market value of assets, the cost approach and market approach are used and the acquisition of fair rental rates with capitalization rate analysis using the riskfree rate and recapture rate. The results of this study obtained an estimate of the market value of assets consisting of land values using the market approach of IDR 44,426,760,000, while the estimated fair rental rate of assets is IDR 4,033,949,808 year and rent per day is IDR 11,051,917. By using the fair rental rates from this study, the estimated contribution to Regional Original Income (PAD) for the last five years is 2,01% of the revenue target calculated for 2020-2024. Keywords: Assets, Rental Value, Cost Approach, Market Approach, Regional Original Income (PAD)